Low-density pedicle screw in adolescent idiopathic scoliosis: a systematic review and meta-analysis of 1,762 patients - Zheng, Bin; Zhou, Qiang; Liu, Xuanwen; Ma, Ke; Qiang, Zhe (Frontiers in Surgery, 2025)
BackgroundHigh-density pedicle screws provide satisfactory correction in adolescent idiopathic scoliosis (AIS) but add to the operative time, blood loss, and cost; low-density constructs may mitigate these burdens and achieve similar correction results. Studies use inconsistent density cutoffs (most often <1.6 screws/level) and report conflicting results; therefore, we performed a systematic review and meta-analysis to clarify the clinical, radiographic, and economic impact of low screw density in patients with AIS.MethodsA systematic review and meta-analysis were conducted following PRISMA guidelines. The PubMed, Web of Science, and Embase databases were searched until December 2024 for comparative studies. The outcomes analyzed included surgical and safety parameters (blood loss, operative time, revision rates, and complications), radiographic outcomes (Cobb angle, correction rate, and thoracic kyphosis), and implant costs. Statistical analyses were performed using RevMan 5.4, with fixed- or random-effects models applied on the basis of heterogeneity (I² threshold < 50%).ResultsTwenty-one studies comprising 1,762 patients met the inclusion criteria. Low-density screws were superior in reducing blood loss [mean difference (MD) = −88.06, P = 0.01] and operative time (MD = −22.27, P = 0.02), with no significant difference in revision rates (P = 0.78) or complications (P = 0.64). No differences were observed between the groups in the final Cobb angle (P = 0.4), Cobb correction rate (P = 0.21), or thoracic kyphosis (P = 0.43). The per-level implant cost was lower (standard mean difference = −1.32, P < 0.00001) in the low-density group.ConclusionCompared with high-density screws, low-density pedicle screws provide comparable radiographic and safety outcomes while reducing the operative time, blood loss, and cost. These findings support the use of low-density constructs in AIS surgery, although the variability in study designs and screw density definitions warrants further research. Future multicenter randomized controlled trials are needed to refine the optimal screw density strategies for treating AIS.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251088403, PROSPERO CRD420251088403.